2004
DOI: 10.1136/jnnp.2003.020651
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following childhood head injury: a population study

Abstract: Objectives: To identify outcomes following head injury (HI) among a population of children admitted to one hospital centre and to compare outcomes between different severity groups. Methods: A postal follow up of children admitted with HI to one National Health Service Trust, between 1992 and 1998, was carried out. Children were aged 5-15 years at injury (mean 9.8), followed up at a mean of 2.2 years post-injury. Parents of 526 injured children (419 mild, 58 moderate, 49 severe) and 45 controls completed quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 25 publications
(18 reference statements)
3
78
1
Order By: Relevance
“…27 They showed a strong correlation between KOSCHI and injury severity, categorized according to the GCS and/or duration of loss of consciousness into mild, moderate, or severe groups. Our results similarly show strong relations between KOSCHI category at hospital discharge and a range of measures of injury severity, namely GCS, length of hospital stay, and PTA.…”
Section: Discussionmentioning
confidence: 99%
“…27 They showed a strong correlation between KOSCHI and injury severity, categorized according to the GCS and/or duration of loss of consciousness into mild, moderate, or severe groups. Our results similarly show strong relations between KOSCHI category at hospital discharge and a range of measures of injury severity, namely GCS, length of hospital stay, and PTA.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Buspirone has been reported to increase dopamine (DA) levels in regions considered essential for cognitive processing such as the prefrontal cortex and hippocampus. 15,48 In addition, numerous studies have shown that DA neurotransmission is important for spatial learning and memory (for excellent reviews, see [10][11][12][13] ). Another potential mechanism may be neuroprotection or restoration of the cholinergic system as evidenced by data showing that 8-OH-DPAT reduced the TBI-induced loss of choline acetyltransferase-positive medial septal cells, which correlated with improved cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Of the surviving children, it is estimated that approximately half exhibit physical, cognitive, and/or psychosocial deficits. [8][9][10] Because of the devastating consequences induced by TBI in a population that could be negatively affected for decades, studies that focus on functional recovery after pediatric TBI are critical.…”
Section: Introductionmentioning
confidence: 99%
“…It can, therefore, fail to differentiate between those who are making rehabilitation progress and those who are not. The King's Outcome Scale for Childhood Head Injury (KOSCHI) 18,19 expands on the GOS approach with better coverage for mild head injury. It differs from the MPAI in two fundamental respects.…”
Section: Discussionmentioning
confidence: 99%